What The Indians Want - Sunday Star (2008)
THE Malaysian Indian community is at a defining moment. Comprising just 1.8 million or roughly 8 at the country's 26 million population it has never been so politically divided. Although the MIC the third largest component party at the Barisan National represents the community in the Government the political allegiance of Indians is split.